Developing Broadcasting Industry Through Glocalisation and Hybridisation - Mutunga, Isaac Mutwiri; Wagumba, Collins (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2019)
This article is a qualitative descriptive study that examines South Korean and East Africa Audio-visual production and distribution policies and regulations. Through analyzing the results of in-depth interviews with audio-visual (broadcast) policymakers, content producers, and audiovisual business owners, this study found that South Korea reviewed regulations and policies that were protectionist in nature to more open and collaborative policies that were in tune with the digital broadcast environment. It recommended that to create successful broadcast industries, developing countries should review their broadcast policies and regulations to be in tandem with digital and media convergence environment as well as give audio-visual industry prominence by establishing ministries that deals with broadcast-related issues to promote locally, to produce content internationally, and also to source for collaboration between local and international producers.